2019
DOI: 10.2478/jomb-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thiol/disulfide homeostasis and oxidant status in patients with hypoparathyroidism

Abstract: Summary Background In this study, we aimed at determining the dynamic thiol/disulfide homeostasis and oxidant balance, and investigating the relation of these parameters to the severity of the disease and the serum calcium levels. Methods 55 patients with iatrogenic hypoparathyroidism follow-ups and 40 healthy volunteers were included in the study. The blood dynamic thiol/sulfide balance, Total Antioxidant Status (TAS), Total Oxidant Status (TOS), Paraoxonase Enzyme Activity (PON) levels were measured in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We detected that native thiol, total thiol, disulphide values, and disulphide/native thiol, disulphide/total thiol ratios of HT patients were significantly higher, while native thiol/ total thiol ratio of these patients were significantly lower compared to controls. Similarly, in the study of Koca et al, (2019), the disulphide, disulphide/native thiol, disulphide/total thiol levels were found higher in a patient with hypoparathyroidism [31]. Mengen et al, (2020) reported high levels of thiol/ disulphide homeostasis and IMA levels in obesity [32].…”
Section: Discussionmentioning
confidence: 60%
“…We detected that native thiol, total thiol, disulphide values, and disulphide/native thiol, disulphide/total thiol ratios of HT patients were significantly higher, while native thiol/ total thiol ratio of these patients were significantly lower compared to controls. Similarly, in the study of Koca et al, (2019), the disulphide, disulphide/native thiol, disulphide/total thiol levels were found higher in a patient with hypoparathyroidism [31]. Mengen et al, (2020) reported high levels of thiol/ disulphide homeostasis and IMA levels in obesity [32].…”
Section: Discussionmentioning
confidence: 60%
“…Currently, numerous markers can be employed to evaluate the level of oxidative stress in a biological system [ 11 , 12 ]. Recently, researchers have focused on thiol-disulfide homeostasis (TDH) as a new marker of oxidative stress [ 13 , 14 , 15 ]. Protein thiol groups are the main antioxidants in plasma [ 16 ].…”
Section: Introductionmentioning
confidence: 99%